Visualizing data. - Fry, Ben, ....- (Beijing : O'Reilly, 2008)
Table of Contents 1 The Seven Stages of Visualizing Data 2 Getting Started with Processing 3 Mapping 4 Time Series 5 Connections and Correlations 6 Scatterplot Maps 7 Trees, Hierarchies, and Recursion 8 Networks and Graphs 9 Acquiring Data 10 Parsing Data 11 Integrating Processing with Java Bibliography Index